Best management practices as an alternative for flood and urban storm water control in a changing climate. Issue 3 (27th July 2015) - Moura, N.C.B.; Pellegrino, P.R.M.; Martins, J.R.S.
Abstract: Global climate models regarding the predicted scenarios of greenhouse gases (GHGs) emissions forecast a general increase in the intensity and frequency of extreme rainfalls. The increase in rainfall run‐off associated with urban growth and more impervious surfaces will lead to unprecedented effects on drainage infrastructures with high risks of flooding. Facing the need for adapting to this future scenario, cities have the opportunity to perform an infrastructural transition when adopting storm water best management practices (BMPs) as sustainable, resilient and landscape‐friendly solutions. This paper presents a qualitative and quantitative study of comparison between BMP techniques and usual detention reservoirs, both as run‐off control strategies. Regarding a case study urban watershed in the Greater São Paulo, Brazil, in which two reservoirs with a total volume of 19.200 m 3 were built, porous sidewalks and bioretention elements have been simulatively located in the contribution area within this basin. The pretended retention volume of these proposed techniques, considering their average porosity, corresponds to 41% of the capacity of the reservoir. This comparative simulation evidences the viability and suitability of storm water BMPs to adapt cities for the impacts of climate change, but their efficiency and performance rely on maintenance and on a design that takes into account the specific local environment.